Helen Andelin and the fascinating womanhood movement - Neuffer, Julie Debra (Salt Lake City, [Utah] : The University of Utah Press, 2014)
"In 1961, Helen Andelin, a disillusioned housewife and mother of eight, languished in a lackluster, twenty-year old marriage. A religious woman, she spent long periods in fasting and prayer asking for help to improve her marriage. While studying a set of women's advice booklets from the 1920s, Andelin had an epiphany that not only changed her life but also affected the lives of millions of American women. She applied the principles from the booklets to her unhappy marriage and found that her difficult and disinterested husband became loving and attentive. He bought her gifts and hurried home from the office to be with her. Their marriage was revitalized. Andelin took her new-found happiness as a sign that God wanted her to share these principles with other women and began teaching classes at her church. The results were dramatic. In 1963, at the urging of her followers, Andelin wrote and self-published Fascinating Womanhood. The book, taken almost word for word from those 1920s advice booklets, sold hundreds of thousands of copies and launched a nationwide organization of classes and seminars led by thousands of volunteer teachers. Countering second-wave feminists in the 1960s, Andelin preached family values and traditional gender roles for women"--
"In 1961, Helen Andelin, a disillusioned housewife and mother of eight, languished in a lackluster, twenty-year old marriage. A religious woman, she spent long periods in fasting and prayer asking for help to improve her marriage. While studying a set of women's advice booklets from the 1920s, Andelin had an epiphany that not only changed her life but also affected the lives of millions of American women. She applied the principles from the booklets to her unhappy marriage and found that her difficult and disinterested husband became loving and attentive. He bought her gifts and hurried home from the office to be with her. Their marriage was revitalized. Andelin took her new-found happiness as a sign that God wanted her to share these principles with other women and began teaching classes at her church. The results were dramatic. In 1963, at the urging of her followers, Andelin wrote and self-published Fascinating Womanhood. The book, taken almost word for word from those 1920s advice booklets, sold hundreds of thousands of copies and launched a nationwide organization of classes and seminars led by thousands of volunteer teachers. Countering second-wave feminists in the 1960s, Andelin preached family values and traditional gender roles for women. She urged women not to have careers, but to become good wives, mothers, and homemakers instead. A woman's true happiness, taught Andelin, could only be realized if she admired, cared for, and obeyed her husband. As her notoriety grew, so did the backlash from her critics. Undeterred, she founded an organization, started a newsletter with a nationwide subscription, and became involved in politics. Andelin spoke to millions of women during a time of social unrest. Her message calling for the return to traditional roles appealed to them during a time of uncertainty and radical social change. This study provides an evenhanded and important look at a crucial, but often overlooked cross-section of American women as they navigated their way through the turbulent decades following the post-war calm of the 1950s. "--
Preface; Introduction; One. Beginnings; Two. The Ideal Woman; Three. Everywoman's Heaven on Earth; Four. Heyday; Five. Enemies; Six. Farmville; Afterword; Notes; Bibliography; Index
Includes bibliographical references and index.
Description based on print version record.
Keywords: Andelin, Helen B; Andelin, Helen B; Anti-feminism -- United States -- History -- 20th century; Housewives -- United States -- Social conditions -- 20th century; Homemakers -- United States -- Social conditions -- 20th century; Sex role -- United States -- History -- 20th century; Women -- United States -- Social conditions -- 20th century; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Andelin, Helen B; Andelin, Helen B. -- Fascinating womanhood; Anti-feminism -- United States -- History -- 20th century; Homemakers -- United States -- Social conditions -- 20th century; Housewives -- United States -- Social conditions -- 20th century; Sex role -- United States -- History -- 20th century; Women -- United States -- Social conditions -- 20th century; Electronic books; Electronic books